2017
DOI: 10.4172/2375-4494.1000354
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Parent s Attitude towards Math and Children s Math Anxiety

Abstract: The objective of the study was to investigate whether there is any relationship between parents' attitude towards math and their children's math anxiety. A cross sectional survey was conducted to explore the math anxiety among the student and their parents' attitude towards math. The data were collected from 200 participants (children n=100; parents n=100). The children age range was from 8-12 years, they were from different schools of Dhaka and parents' age range was from 27 to 55 years. "Math Anxiety scale f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Nitrogen-vacancy center, image reproduced under the terms of the Creative Commons Attribution 4.0 International license. [267] Copyright 2017, The Authors. Published by MDPI.…”
Section: Map Of Energy Transport Within Plasmonic Gapmentioning
confidence: 99%
“…Nitrogen-vacancy center, image reproduced under the terms of the Creative Commons Attribution 4.0 International license. [267] Copyright 2017, The Authors. Published by MDPI.…”
Section: Map Of Energy Transport Within Plasmonic Gapmentioning
confidence: 99%
“…Por eso, es común encontrar un importante contingente de estudiantes quienes dicen que no les gusta la matemática y les cuesta aprenderla (Martínez-Padrón, 2016, 2021. Otras razones se deben a la actitud de los padres y madres frente a sus hijos e hijas, a quienes también les causan una ansiedad matemática (Haque y Farhana, 2017) que puede decantar en sentimientos de frustración y rabia. De manera que cualquiera sea el disparador de tales situaciones, siempre hay que apostar por encontrar oportunidades para ir a su encuentro, arrostrarlas y localizar las soluciones plausibles demandadas cuando ese recibe la formación escolar correspondiente.…”
Section: Afrontando Adversidades En Matemáticasunclassified
“…As far as parents are concerned, Mutodi and Ngirande (2014) confirmed that students who accredited their success to the interest, self-confidence, as well as family background, have a chance to come up with higher achievements than those who point their academic success to chance and natural talent. Indeed, Haque & Farhana (2017) and Makeo (2013) have investigated and found out that parents 'perception of mathematics has an influence on their children's perception, and hence influence their performance. Moreover, there is no contradiction between mathematics that takes place in the classroom compared to that one that takes place outside the classroom (Schoenfeld, 1989).…”
Section: Introductionmentioning
confidence: 99%